Reinforcement contribution to the behavior of low-rise concrete walls (2014)
Based on steel strains recorded during shake table tests of six wall specimens, the effect and contribution of steel reinforcement to peak shear strength and displacement capacity of low-rise concrete walls is assessed and discussed. The experimental program included four variables such as wall geometry, concrete type, web steel ratio and type of web reinforcement. Wall response was assessed through effective steel strains in vertical reinforcement, efficiency factors of wall reinforcement, contribution of web horizontal reinforcement to wall shear strength, and the effect of type of web reinforcement to wall displacement.